Tailored graphene systems for unconventional applications in energy conversion and storage devices. Issue 1 (20th October 2014) - Hu, Chuangang; Song, Long; Zhang, Zhipan; Chen, Nan; Feng, Zhihai; Qu, Liangti
Abstract : Graphene-based materials have shown great potential in various fields across physics, chemistry, biology, and electronics, due to their unique electronic properties, facile synthesis, and ease of functionalization. Abstract : Graphene-based materials have shown great potential in various fields across physics, chemistry, biology, and electronics, due to their unique electronic properties, facile synthesis, and ease of functionalization. In this review, we summarize the significant advances in tailored graphene systems for the recently developed unconventional energy conversion and storage devices reported by our group and others, namely focused on their tunable and controllable preparation and remarkable applications in new types of supercapacitors, lithium ion batteries, photovoltaic cells, and other emerging generators. This featured article also highlights the working principles and outlines the problems hindering the practical applications of graphene-based materials in these energy-related devices. Future research trends towards new methodologies in the design and synthesis of graphene-based systems with unique properties for emerging energy storage and energy conversion devices are also proposed.